Total Factor Productivity and the Real Exchange Rate in a Small Open Economy: The Relative Importance of Permanent and Transitory Shocks - Göran Hjelm (Lund University, School of Economics and Management, Department of Economics, 2001)
Recent theoretical research suggest that monetary shocks might play an important role in explaining movements in the real exchange rate in the short and medium run. Empirically, the contribution of transitory (monetary) disturbances in explaining the variance decomposition of real exchange rates has varied substantially in the recent literature. In this paper, we construct new quarterly series of total factor productivity for Sweden and Japan. We find that these series and the real exchange rate are cointegrated and estimate a so called common trends model. The two permanent shocks are identified as being productivity shocks of Japan and Sweden, respectively, and it is shown that the transitory shock can be interpreted as being of monetary origin. Contrary to the predictions of recent theoretical models, the transitory shocks explains only a minor part of the movements in the real exchange rate (7.2 percent after two quarters at most) which implies that productivity shocks clearly dominate the picture
Keywords: C32; F31; O47; 330; Real exchange rates; Total factor productivity; Common trends